Diffuse Large B-Cell Lymphoma: Clinical Presentation and Treatment Outcomes From the OncoCollect Lymphoma Registry - Nair, Reena; Bhurani, Dinesh; Rajappa, Senthil; Kapadia, Asha; Reddy Boya, Rakesh; Sundaram, Subramanian; Menon, Hari; Raman, Ganapathi S.; Seshachalam, Arun; Nimmagadda, Ramesh (Frontiers in Oncology, 2022)
Background Diffuse large B-cell lymphoma (DLBCL) is the commonest subtype of lymphoma, standard CHOP was the treatment of choice, 42% of patients received rituximab, and 29% of patients were lost to follow-up during therapy, were reported in a study that collected retrospective data at 13 public and private hospitals for patients diagnosed with lymphoma between January 2005 and December 2009. The OncoCollect Registry was set up in 2017 to address the challenges in the collection of retrospective data through chart review, recording access to anthracycline and rituximab-based treatment, and to study outcomes and any improvement in the patient follow-up. Methodology The OncoCollect Lymphoma group registry was set up at a national level with 9 participating centers. Lymphoma patients registered at these centers between 2011 and 2017 were included. The clinical features, prognostic stratification, associated comorbidities, response to first-line treatment, and 3-year outcomes of adult patients with DLBCL were analyzed. Results Of the 5,886 lymphoma patients registered in the OncoCollect registry, 2,581 (44%) had DLBCL. A total of 1,961 were evaluable for frontline therapy. The median age at presentation was 57 years. Gender ratio was 1.6:1. At presentation, 43% were early stage, 70% had low and low intermediate IPI, 53% had extranodal disease, and 30.9% had one or more comorbidities (data available for 1,136 patients). The commonest extra nodal site was gastro-intestinal (23.98%) followed by head and neck (19.24%). The overall response rate was 79.29%. Complete remission was seen in 61.75%, partial response in 17.5%, stable disease in 4.3%, and progression in 7.9%. Patients who received anthracycline-based therapy (86.7%) and rituximab-based therapy (83.7%) had a 3-year event-free survival (EFS) of 69.67% and 68.48%, respectively. With a median follow-up of 33 months, the 3-year overall Survival (OS) and EFS were 75.37% and 66.58%, respectively. Conclusions DLBCL remains the commonest (44%) lymphoma subtype and is curable with standard anthracycline- and rituximab-based therapies. The availability of rituximab has increased the proportion of patients receiving standard chemoimmunotherapy.